2017
DOI: 10.1007/s10018-017-0189-2
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the non-linearity between national income and environmental pollution: international evidence of Kuznets curve

Abstract: This paper analyzes how national income (per capita real GDP) influ- ences the environmental pollution (per capita CO2 emissions) using a very heterogenous sample composed by 120 countries during the 2000–2009 period. We first apply a panel unit root test suggested by Im et al. (J Econometr 115(1):53–74, 2003) to examine the stationarity properties of CO2 emissions and GDP and then a two-step generalized method of moments (GMM) estimator, paying particular attention to the non-linearity of the national income–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 72 publications
3
17
0
Order By: Relevance
“…The empirical validity of this premise is inconclusive. While some studies have been able to demonstrate the existence of an EKC in some regions or countries (Apergis and Ozturk, 2015;Jebli et al, 2016;Hanif and Gago-de Santos, 2017;Barra and Zotti, 2018), other authors find mixed evidence between the expansion of industrial production and environmental degradation (Shuai et al, 2017;Luo et al, 2017). Even some papers find no evidence for such a hypothesis (Xu, 2018;Baek, 2015;Zilio and Caraballo, 2014).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…The empirical validity of this premise is inconclusive. While some studies have been able to demonstrate the existence of an EKC in some regions or countries (Apergis and Ozturk, 2015;Jebli et al, 2016;Hanif and Gago-de Santos, 2017;Barra and Zotti, 2018), other authors find mixed evidence between the expansion of industrial production and environmental degradation (Shuai et al, 2017;Luo et al, 2017). Even some papers find no evidence for such a hypothesis (Xu, 2018;Baek, 2015;Zilio and Caraballo, 2014).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Even though the EKC argues that the relationship between economic activity and environmental degradation has an inverted U-shape, there has been empirical evidence to the contrary. Many studies have supported the EKC [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33], but some have not [34][35][36][37][38][39][40][41][42][43][44][45]. Further, several studies have found mixed results (supporting the EKC hypothesis for some countries/pollutants but not for other countries/pollutants) [46][47][48][49][50][51][52][53][54][55] (see Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…For this particular environmental measure, an EKC was corroborated in the studies of Holtz-Eakin and Selden (1995), Galeotti and Lanza (1999), Heil and Selden (2001), Cole (2004), Galeotti et al (2006), andParajuli et al (2019), among others, in contradiction with the results obtained in Shafik and Bandyopadhyay (1992), Galeotti and Lanza (2001), York et al (2003), and Nutakor et al (2020), for example. Other researches such as Sengupta (1996) and Martinez-Zarzoso and Bengochea-Morancho (2004) find a cubic N-shaped relationship, whereas Barra and Zotti (2018) points out that preliminary evidence validates the Kuznets's hypothesis, although this relationship turned out to be misleading once the issue of (non)-stationarity has been taking into account.…”
Section: Literature Overview On the Ekcmentioning
confidence: 88%